First record of young‐of‐the‐year smooth hammerhead ( Sphyrna zygaena ) in coastal waters of Galicia, northwest Spain - Xabier Pin; Kenn Papadopoulo; Pablo Covelo; Gonzalo Mucientes (Journal of Fish Biology, 2026)
The smooth hammerhead ( Sphyrna zygaena ) is typically considered an oceanic species and is only rarely observed in the cooler coastal waters of the northeastern Atlantic. On 20 December 2024, a juvenile S. zyganea was captured at 25 m depth in the inner Ría de Pontevedra (Rías Baixas, northwest Spain). This represents the first verified record of a young‐of‐the‐year individual in Galicia, and potentially across the entire Iberian Peninsula. This observation, together with four confirmed adult sightings in Galician waters in recent years, indicates the sporadic presence of the species far beyond its recognised nursery and distributional range. Such occurrences may reflect an emerging northward or inshore shift, potentially linked to climate‐driven changes in regional oceanographic conditions. Documenting these atypical events enhances our understanding of hammerhead shark ecology in temperate Atlantic systems and underscores the need to identify potential nursery habitats within European waters.

Solitary dolphins in Spain and recommendations for their management - Laetitia Nunny; Mónica González; Alfredo López; Pablo Covelo; Jose Antonio Martínez-Cedeira; Xabier Pin; Uxía Vázquez; María Macías González; Paula San Martín Lorén; Mark P. Simmonds (Animal Behaviour, 2026)

First Confirmed Record of the Smalltooth Sand Tiger, Odontapis Ferox, in Galicia (NW Spain) - Gonzalo Mucientes; Nair Vilas-Arrondo; Giulia Secci-Petretto; Uxía Vázquez; Xabier Pin; Alfredo López; L. Filipe C. Castro; Elsa Froufe (Thalassas: An International Journal of Marine Sciences, 2023)
The smalltooth sand tiger shark Odontaspis ferox (Risso, 1810) appears to have an extensive and fragmented distribution in tropical and warm-temperate worldwide oceans. One female of O. ferox was caught and released by a small-scale fishery vessel in Ría de Arousa (Northwest of Spain), subsequently stranded still alive on the coast (42°33’18.4"N 8°49’18.3"O) after a few hours. The individual (336 cm total length, weight ~ 300 kg) was identified based on a collection of features including the characteristic dentition, body morphology and by molecular assignment. This is the first confirmed record of O. ferox in Galician waters. This finding complements the knowledge of the geographic distribution and occurrence of this rare and sparse species in the Northeastern Atlantic.